PEMBELAJARAN MODEL CONTEXTUAL TEACHING AND LEARNING DENGAN MEMANFAATKAN LINGKUNGAN SEBAGAI SUMBER BELAJAR IPS DALAM MENINGKATKAN PRESTASI BELAJAR SISWA - Harry Surahman (IKIP Budi Utomo Malang, 2018)
Education in Indonesia is still dominated by the view that knowledge of the facts that must be memorized. This has resulted in students becoming passive learners. Therefore, teachers are expected to select and apply the learning model appropriate to the situation and condition of learning. This is done to avoid failing students in learning, due to a lack of understanding of the concept as a whole. Contextual Teaching and Learning (CTL), as the concept of learning strategies that help teachers link between what is taught by the empirical facts known to the students and encourage students to create relationships through the application of knowledge in everyday life.The problem in this study are: (1) Learning by Utilizing CTL Model Environment as a Learning Resource IPS experimental class could be better than the conventional model in classroom learning control (2) Is the student response to learning with the use CTL as the Source of Learning Environment IPS better than Using Conventional.The design of such studies are experimental research with two groups pretest-posttest design. The subjects were students of class VII SMP Yadika Bangil Pasuruan the number of 25 students for each class experimental and control classes. The instrument used to collect data include questionnaires, achievement test, observation, and documentation. Data analysis using SPSS 17 software. Based on a statistical analysis of the study showed that there is a significant difference between the improvement of student learning outcomes in the classroom experiments with the control class. In more detail the following results were obtained: (1) The results show completeness minimal thorough standart (KKM) student learning after the learning process using CTL model to use the environment as a source of social studies with a completeness of 88%, (2) the activity of the students participating in learning activities with CTL using the environment as a learning resource better than the students who take conventional learning, (3) Students responded positively to the application of learning CTL model by using the environment as a source of learning, (4) barriers were found during the study that although a small percentage of his lack of time (lesson 2 hours x 40 minutes) so that students who have not completed the task in school serve as homework. Based on these findings it can be concluded that the CTL model by using the environment as a learning resourcein learning the topic of population and economic activity patterns of land use based on the physical condition of the Earth’s surface can improve student learning outcomes SMP Yadika Bangil.